2006
DOI: 10.1892/0891-6640(2006)20[1389:roccel]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Response of Canine Cutaneous Epitheliotropic Lymphoma to Lomustine (CCNU): A Retrospective Study of 46 Cases (1999–2004)

Abstract: Given the high response rate and well tolerated protocol, prospective studies are warranted to investigate the utility of CCNU alone or in multi-agent protocols for the treatment of ELSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
91
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(99 citation statements)
references
References 19 publications
5
91
2
1
Order By: Relevance
“…The mean starting CCNU dose was 70.6 mg/m 2 (median, 71.4 mg/m 2 ; range, 54.9-81.3 mg/m 2 ) and the median number of CCNU doses administered was 3 (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Seven (28%) dogs in group A and 9 (36%) dogs in group B received CCNU every 28 days alternating with vinblastine.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The mean starting CCNU dose was 70.6 mg/m 2 (median, 71.4 mg/m 2 ; range, 54.9-81.3 mg/m 2 ) and the median number of CCNU doses administered was 3 (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Seven (28%) dogs in group A and 9 (36%) dogs in group B received CCNU every 28 days alternating with vinblastine.…”
Section: Resultsmentioning
confidence: 99%
“…11 Previously published retrospective studies describing the use and toxicity of CCNU in dogs reported inconsistent measurement of liver enzyme activity during therapy, making the true incidence and severity unclear. 2,3,10,11 Additionally, some dogs in these previous studies had increased liver enzyme activity before starting CCNU therapy, further confounding results. Nonetheless, increased liver enzyme activity remains a clinically relevant problem for veterinarians who prescribe CCNU.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, systemic osteolysis with punched-out sites is often seen in multiple myeloma due to osteoclast-activating factor (OAF) produced by plasmacytes and mature B cells. Hematological malignancies such as myeloma and adult T-cell lymphoma/ leukemia can induce bone lesions because many of the factors that increase osteoblast formation and activation are produced by lymphocytes and monocytes [11]. For example, lymphocytes can produce interleukin-1 (IL-1), IL-6, colony-stimulating factors, and lymphotoxin.…”
mentioning
confidence: 99%